Implementasi Gerobak Pintar dengan PLTS dan IoT untuk Peningkatan Produktifitas dan Kualitas Pertanian Desa Sidopekso Kabupaten Probolinggo - Sulistiyanto, Sulistiyanto; Karim, Abdul; Mahbubi, M. (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to improve agricultural productivity and quality through the application of renewable energy technology and the Internet of Things (IoT) in Sidopekso Village, Probolinggo Regency. The implementation methods included needs assessment, prototype design and assembly, participatory training, field trials, and performance evaluation, analyzed descriptively using a qualitative approach. The results of this program showed that the solar-powered smart cart was able to supply electricity for agricultural equipment, support an automated irrigation system based on soil moisture sensors, and provide a facility for digital agricultural data recording. Participant evaluations indicated a 46% increase in knowledge and a 28% improvement in water-use efficiency compared to conventional methods. This innovation not only offers a practical and environmentally friendly solution but also promotes energy self-sufficiency and the adoption of smart technologies in rural agriculture. In the future, this solar-powered IoT-based smart cart model has the potential to be replicated in other regions with similar agricultural characteristics.